2018
DOI: 10.1590/1806-9061-2018-0767
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Licorice (Glycyrrhriza glabra) Root on Performance, Some Serum Parameters and Antioxidant Capacity of Laying Hens

Abstract: The current study was conducted to determine the effects of the licorice root (Glycyrrhriza glabra) in laying hens diets on performance, egg cholesterol, some plasma parameters and antioxidant capacity. One hundred, 40-week old laying hens were divided into four groups, each group consisted of 25 hens and were placed in individual cages. The mean of the initial body weight of laying hens was 1829.18±9.595 g. Commercial laying hen diet was supplemented with 0, 0.5, 1.0 and 2.0% levels of licorice root powder an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This decrease of LDL cholesterol has been attributed to the action of liquorice that protects LDL cholesterol from oxidation by inhibiting the enzymes like cyclooxygenase and lipoxygenase which in turn inhibit lipid peroxidation (Craig 1999). In another study, the supplementation of liquorice root powder at different levels in chicken diet resulted in significant increase in plasma HDL cholesterol, while no significant changes were observed in plasma LDL cholesterol, total cholesterol, and triglyceride in broiler chicken (Dogan et al 2018a).…”
Section: Triglyceride Cholesterol Vldl Ldl and Hdl Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease of LDL cholesterol has been attributed to the action of liquorice that protects LDL cholesterol from oxidation by inhibiting the enzymes like cyclooxygenase and lipoxygenase which in turn inhibit lipid peroxidation (Craig 1999). In another study, the supplementation of liquorice root powder at different levels in chicken diet resulted in significant increase in plasma HDL cholesterol, while no significant changes were observed in plasma LDL cholesterol, total cholesterol, and triglyceride in broiler chicken (Dogan et al 2018a).…”
Section: Triglyceride Cholesterol Vldl Ldl and Hdl Concentrationsmentioning
confidence: 99%
“…The dietary supplementation of liquorice root extract or powder in broiler chicken and Japanese quails increased plasma glucose level in a dose dependent manner (Al-Daraji 2012; Dogan et al 2018a;Dogan et al 2018b). This increase in glucose level may be attributed to glycyrrhizin, a saponin glycoside, that is found to be sixty times sweeter than sucrose (Roshan et al 2012).…”
Section: Effect On Blood Glucosementioning
confidence: 99%
“…A study performed on hundred 40-week-old laying hens showed that the diets supplemented with LE improved the production of functional eggs and modulated the productive performance of laying hens by lowering the egg cholesterol level, some plasma parameters (reduction in LDL and egg-yolk cholesterol level with an increase in the HDL level and total antioxidant capacity of plasma [61]. Scientific literature has witnessed the global impact of this herb on the performance, carcass traits, and meat quality of poultry, when their diet is supplemented with licorice ( G. glabra ) either in feed and/or in drinking water [6].…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%
“…4,5) The steric structure of the C-and E-rings of triterpenoids and the functional group at position C-30 are responsible for the taste of triterpenoids in licorice. 6) GL is an important pharmacological compound because it exhibits antiviral, 7,8) antioxidant, 9,10) anti-atopic dermatitis, 11) anti-inflammatory, 12) and immunomodulatory activity 13) ; prevents cancer metastasis and chemoresistance 14) ; and protects against glucocorticoidinduced osteoporosis. 15) From the perspective of pharmacokinetics, the bioavailability of GL is low 16) because it is metabolized to its corresponding aglycone with or without chemical modification by several enterobacteria resulting in metabolites with various actions.…”
Section: Introductionmentioning
confidence: 99%